PENYELENGGARAAN MAKANAN DAN INDIKASI FOOD BORNE DISEASE PADA SANTRI DI PONDOK PESANTREN AINUL YAQIN - Dini Junita; Merita Merita (Jurusan Gizi Poltekkes Kemenkes Makassar, 2021)
Food services in Islamic boarding schools is a series of activities from menu planning to food distribution, in order to meet the needs and achieve optimal health status of students. It is important to pay attention to the supervision of food preparation because large food products are very susceptible to contamination and cause food borne disease. This study generally aims to identify and analyze the food administration system and food-related diseases at the Ainul Yaqin Islamic Boarding School. This research is a qualitative observational survey method with a descriptive approach using primary and secondary data. Primary data in this study are data taken directly in the field during research. Food production hygiene hygiene data used observation sheets, personal hygiene data for food handlers was known through interviews using questionnaires, data on characteristics and incidence of food borne disease in students using questionnaires and interviews. The results of this research activity indicate that the description of the characteristics and personal hygiene of food handlers at the Ainul Yaqin Islamic Boarding School is still less than the standard both in terms of infrastructure, and awareness and behavior of hygiene sanitation. The sanitation of food management at Pondok Pesantren Ainul Yaqin is not yet organized, and is spontaneous without planning. The description of the incidence of food borne disease in Ainul Yaqin Islamic boarding school has a high risk, seen from having experienced symptoms / indications. As well as food handlers need to be trained on food safety to increase knowledge and practice of hygiene and sanitation. And it is necessary to create a culture of Clean and Healthy Behavior in the lives of the Ainul Yaqin Islamic Boarding School students.